(untitled) (Annals of Medical Research, 2021)
Aim: Pediatric diseases affect both the children and their families psychologically. Parents may experience stress with the development of these diseases. The autonomic nervous system is one of the systems activated in response to stress. The current study aimed to investigate the activity of sympatho-vagal axis in mothers of children with pediatric diseases. Materials and Methods: Following ethical consent, the study was carried out on the mothers of healthy children (healthy, n=25) and children with cancer (cancer, n=25), and children with non-cancer disease (non-cancer, n=25). Heart rate variability was used to assess autonomic nervous system’s activity by taking a 5 min electrocardiogram recording. Heart rate variability (HRV) parameters such as standard deviation of RR intervals, mean square of successive RR interval differences, and low frequency/high frequency band were calculated by special software. Results: Standard deviation of NN intervals (healthy 37±2, non-cancer 35±2, cancer 35±3), root mean square of successive RR interval differences (healthy 33±3, non-cancer 30±3, cancer36±5), LF/HF (healthy 1.69±0.21, non-cancer 1.40±0.17, cancer 1.30±0.16) and other HRV findings (p>0.05) were not different among the mothers. Systolic blood pressures were higher (p=0.000) in the mothers of healthy children (115±2) than in mothers of children with non-cancer diseases (102±2) and with cancer (109±2). Diastolic blood pressures were higher (p=0.022) in mothers of healthy children (79±2) compared to mothers of children with non-cancer disease (73±1), but not from those mothers of children with cancer (78±2). Conclusion: Mothers did not differ in terms of HRV parameters, suggesting that children, whether healthy or sick, are always perceived as a great responsibility by the mothers.